Bioethics Across the Globe Rebirthing Bioethics - Akabayashi, Akira (Springer Nature, 2020)
This open access book addresses a variety of issues relating to bioethics, in order to initiate cross-cultural dialogue. Beginning with the history, it introduces various views on bioethics, based on specific experiences from Japan. It describes how Japan has been confronted with Western bioethics and the ethical issues new to this modern age, and how it has found its foothold as it decides where it stands on these issues. In the last chapter, the author proposes discarding the overarching term 'Global Bioethics' in favor of the new term, 'Bioethics Across the Globe (BAG)', which carries a more universal connotation. This book serves as an excellent tool to help readers understand a different culture and to initiate deep and genuine global dialogue that incorporates local and global thinking on bioethics. Bioethics Across the Globe is a valuable resource for researchers in the field of bioethics/medical ethics interested in adopting cross-cultural approaches, as well as graduate and undergraduate students of healthcare and philosophy.